Fit for purpose: do we have the right tools to sustain NTD elimination?. Issue 10 (December 2015) - Reimer, Lisa; Adams, Emily; Paine, Mark; Ranson, Hilary; Coleman, Marlize; Thomsen, Edward; MacPherson, Eleanor; Hollingsworth, T; Kelly-Hope, Louise; Bockarie, Moses; Ford, Louise; Harrison, Robert; et al.
Abstract Priorities for NTD control programmes will shift over the next 10-20 years as the elimination phase reaches the 'end game' for some NTDs, and the recognition that the control of other NTDs is much more problematic. The current goal of scaling up programmes based on preventive chemotherapy (PCT) will alter to sustaining NTD prevention, through sensitive surveillance and rapid response to resurgence. Anew suite of tools and approaches will be required for both PCT and Intensive Disease Management (IDM) diseases in this timeframe to enable disease endemic countries to: 1. Sensitively and sustainably survey NTD transmission and prevalence in order to identify and respond quickly to resurgence. 2. Set relevant control targets based not only on epidemiological indicators but also entomological and ecological metrics and usedecision support technology to help meet those targets. 3. Implementverified and cost-effective tools to prevent transmission throughout the elimination phase. Liverpool School of Tropical Medicine (LSTM) and partners propose to evaluate and implement existing tools from other disease systems as well as new tools in the pipeline in order to support endemic country ownership in NTD decision-making during the elimination phase and beyond.